Influence of Adrenal Subclinical Hypercortisolism on Hypertension in Patients with Adrenal Incidentaloma - Oki, K.; Yamane, K.; Nakanishi, S.; Shiwa, T.; Kohno, N. (Experimental and Clinical Endocrinology & Diabetes, 2012)
The purpose of our study was to clarify whether subtle cortisol-producing tumors, such as not only subclinical Cushing’s syndrome (SubCS) but also subclinical hypercortisolism (SH), influence the prevalence of hypertension, since numerous basic research studies have noted that glucocorticoid excess influences blood pressure.80 patients with adrenocortical adenomas (39 women and 41 men; mean age 62.1 years) were enrolled. SubCS was diagnosed using a diagnostic criteria, and SH was diagnosed as the presence of a serum cortisol level greater than 50 nmol/L following 1-mg dexamethasone suppression test (DST).SubCS, SH, or non-functioning adrenocortical adenoma (NF) was diagnosed in 14, 13, or 53 patients, respectively. The prevalence of hypertension differed significantly among the diagnoses (SubCS, 78.6%; SH, 84.6%; NF, 39.6%; P=0.002), whereas no differences in other clinical characteristics such as age, sex, or waist girth were observed. The patients with SH had an 11.7-fold increased risk (95% confidence interval: 1.9–72.7, P=0.009) and those with SubCS had a 9.5-fold increased risk (95% confidence interval: 1.9–48.3, P=0.007) for hypertension compared to those with NF using a multivariate analysis.We demonstrated that subtle cortisol-producing tumors, such as SH as well as SubCS, were an independent risk factor for hypertension. The cut-off value of the 1-mg DST would be appropriate to predict the development of hypertension.
Keywords: subclinical Cushing’s syndrome; hypertension; cortisol; adrenal tumor